United States. Army of the Potomac. 6th Corps order and letterbook - United States. Army of the Potomac. Corps, 6th (1862-1865)
Volume comprising an order and letterbook (1862 September 24-1865 March 13) of the medical department, U.S. Army, 6th Corps (Army of the Potomac).
Collection material in English.
Keywords: United States. -- Army of the Potomac; United States -- History -- Civil War, 1861-1865 -- Medical care